ANALISIS PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Pegawai Non Medis RSUD Kepanjen Kabupaten Malang) - -, Sajudinnoor (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study is to investigate and analyze the effect of compensation on employee performance as well as to identify and analyze the effect of compensation on employee performance are moderated by the variable satisfaction. The population in this study is still non-medical hospital employees Kepanjen Malang, amounting to 120 people. Of the population sample by using Slovin formula, ie by 55 respondents. The results showed that compensation, satisfaction, and the absolute value of the difference in compensation to the satisfaction of the employees associated with employee performance. compensation is positively related to employee performance. absolute difference between the value of the variable compensation with significant satisfaction in the regression. Absolute value of the difference variable compensation with satisfaction positive effect on employee performance.. Keyword: Compensation, Satisfaction, Performance